2021
DOI: 10.3390/ma14081884
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation for Evaluating Fracture Entropy of a Polymer Material under Various Combined Stress States

Abstract: Herein, the stress-state dependence of fracture entropy for a polyamide 6 material is investigated through molecular dynamics simulations. Although previous research suggests that a constant entropy increase can be universally applied for the definition of material fracture, the dependence of stress triaxiality has not yet been discussed. In this study, entropy values are evaluated by molecular dynamics simulations with varied combined stress states. The calculation is implemented using the 570,000 all-atom mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This study investigates the time evolutions of covalent bond dissociation and fracture behavior of a thermosetting polymer based on molecular dynamics (MD) simulation, which is essential for elucidating microscopic damage mechanisms of matrix crack and transverse crack in CFRPs. MD simulation has been applied to polymers [ 7 , 8 , 9 , 10 ], reinforcements [ 11 , 12 ], and their composites [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], which have quantitatively reproduced thermomechanical properties near equilibrium state such as density, Young’s modulus, and glass transition temperature. Characteristics in the higher-strain region, where covalent bond dissociation is involved, remain challenging to simulate.…”
Section: Introductionmentioning
confidence: 99%
“…This study investigates the time evolutions of covalent bond dissociation and fracture behavior of a thermosetting polymer based on molecular dynamics (MD) simulation, which is essential for elucidating microscopic damage mechanisms of matrix crack and transverse crack in CFRPs. MD simulation has been applied to polymers [ 7 , 8 , 9 , 10 ], reinforcements [ 11 , 12 ], and their composites [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], which have quantitatively reproduced thermomechanical properties near equilibrium state such as density, Young’s modulus, and glass transition temperature. Characteristics in the higher-strain region, where covalent bond dissociation is involved, remain challenging to simulate.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the fatigue life estimation of CFRP was assessed by considering both confidence levels and reliability. Koyanagi et al [36][37][38][39][40] recently formulated a computational approach that integrates entropy damage to analyze the failure mechanism of a viscoelastic matrix and CFRP cross-ply laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics simulations (MD) have become a useful tool for clarifying the causes of experimental phenomena [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Regarding the mechanical properties of polymers, Fan et al predicted the thermomechanical properties of epoxy [19] and Fujimoto et al investigated the impact fracture of poly-methyl-methacrylate (PMMA) and polycarbonate (PC) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Bhowmik et al calculated the specific heat of polymers, which is related to thermodynamic entropy, via MD simulations. Takase et al [25] analyzed the fracture entropy generation of polyamide 6 (PA6) using MD simulations and observed that the fracture entropy generation under multiaxial conditions was almost consistent. The entropy generation and free volume change were observed to depend on mechanical loading.…”
Section: Introductionmentioning
confidence: 99%